Prevalence of tumor BRCA1 and BRCA2 dysfunction in unselected patients with ovarian cancer - Roshni D. Kalachand; Ciaran O'Riain; Sinead Toomey; Aoife Carr; Kirsten M. Timms; Sharon O'Toole; Stephen Madden; Mark Bates; John J. O'Leary; Noreen Gleeson; Dearbhaile O'Donnell; Liam Grogan; et al. (Korean Society of Obstetrics and Gynecology, 2020)
Objective The therapeutic benefits of poly(ADP-ribose) polymerase inhibitors highlight the need to evaluate BRCA1/2 defects in tubal/ovarian cancer (OC). We sought to determine the pattern and disease characteristics associated with tumor BRCA1/2 mutations and BRCA1 methylation in women with OC. Methods We obtained 111 OC specimens from 2 university hospitals and assessed BRCA1/2 mutations and BRCA1 methylation in tumor DNA. The frequency and pattern of BRCA1/2 defects were examined. Associations between patient/disease characteristics and BRCA1/2 defects were ascertained (Fisher's exact test). Platinum-free interval (PFI), progression-free survival (PFS), and overall survival (OS) based on the underlying BRCA1/2 defect were determined (Kaplan-Meier analysis [log-rank test]). Results We observed a BRCA1/2 dysfunction rate of 40% (28/70) in high-grade serous tubal/ovarian cancer (HGSC), including 14.3% BRCA1 methylation (n=10), 7.1% BRCA1 mutation (n=5), and 18.6% BRCA2 mutation (n=13). Defects in BRCA1/2 genes were associated with stage III/IV HGSC (BRCA1 methylation: P=0.005 [stage III/IV] and P=0.004 [HGSC]; BRCA1/2 mutation: P=0.03 [stage III/IV] and P<0.001 [HGSC]). Patients with BRCA1/2-mutated cancers showed improved OS (hazard ratio [HR], 0.65; 95% confidence interval [CI], 0.43-0.99; P=0.045) and a trend toward improved PFI (HR, 0.48; 95% CI, 0.22-1.06; P=0.07) and PFS (HR, 0.72; 95% CI, 0.51-1.03; P=0.07). No survival differences were observed between BRCA1-methylated and BRCA1/2 wild-type non-BRCA1-methylated cancers. Conclusion We observed a high tumor BRCA1/2 dysfunction rate in HGSC with a unique predominance of BRCA2 over BRCA1 mutations. While BRCA1/2 mutations conferred survival benefits in OC, no such association was observed with BRCA1 methylation.